Multi-sensor remote sensing of effusive eruption dynamics and lava flow morphology at Great Sitkin Volcano, Alaska - Dietterich, Hannah R.; Plank, Simon Manuel; Loewen, Matthew W (2023)
Remote sensing of effusive eruptions is critical for monitoring and assessment of lava flow morphology and dynamics. For remote eruptions, such as the 2021-present explosive and effusive eruption of Great Sitkin Volcano in the central Aleutian Islands, Alaska, remote sensing provides our primary dataset for characterizing eruptive behavior and assessing hazards. Following precursory seismicity, SO2 emissions, and elevated surface temperatures, a vulcanian eruption at Great Sitkin on 26 May 2021 marked the onset of an ongoing eruptive period (as of submission). More than 14 months of lava effusion has filled most of the volcano’s summit crater with lava (~1.1 km in diameter) and spilled down the upper flanks of the edifice, forming flow lobes up to 1.2 km long. We integrate a time series of multi-sensor remote sensing from thermal, optical, and radar sensors to track the three-dimensional emplacement and thermal emissions of ongoing lava effusion at Great Sitkin. Very-high-spatial-resolution (<1-meter) synthetic aperture radar imagery and bistatic acquisitions from TerraSAR-X/TanDEM-X and optical imagery from Maxar, including stereo and shortwave infrared acquisitions, have allowed detailed quantification of the lava flow morphology (including flow extent, thickness, volume, and surface morphology) through time. We also analyze multi-sensor thermal imagery (MODIS, VIIRS) to track the thermal evolution of the lava flow at higher temporal resolution (hours) but coarser spatial resolution (0.4 - 1 km). Higher spatial resolution (90-meter) night-time Landsat-8/9 data allow more detailed analysis of thermal activity. Our results combine with modeling to indicate effusion rates of up to 7 m³/s, viscosities of ~10^10 Pa s, and the evolving emplacement dynamics from endogenous to exogenous growth and interaction with both glacial ice and topography. We compare these to corresponding geochemical and geophysical datasets, including samples from the 2021 explosive phase and past Great Sitkin eruptions, to assess eruption ...